Programa Bolsa Família (PBF): construções discursivas de ex-participantes residentes em Alagoas - Souza, Wagner Leite de (2020)
The present master’s research is located in the field of Political Psychology and it debates the “Programa Bolsa Família” (PBF). Since its implementation, PBF was signified in most diverse ways (emancipatory program, assistance politics, electioneering program) overall, by politicians from diverse parties or by researchers from diverse theoretical fields, expressing conflicting conceptions both in the social aspect and regarding strategies of social transformation. In this paper, we research the discursive construction of PBF made by former participants of the Program, focusing on the relation between the discourse that was built and the way they locate in the domination relations of which They are part. This way, we aim to: a) understand how former participants conceive the PBF, in terms: (1) of the demands directed to PBF; (2) of the way they built their demands; (3) of the way they conceive the local management strategies of PBF; (b) understand how the individuals recognize themselves in the dominance relations; c) discuss the relevance of PBF to the expansion of democracy. Twenty former participants of PBF were interviewed, all of which are residents of the four counties of Alagoas that presented the higher number of voluntary withdraws, namely: Campo Alegre, Santana do Mundaú, Água Branco e Coqueiro Seco. The method of data production adopted was “Oral history”, the interviews were recorded and transcribed and, subsequently, analyzed in the light of the discourse analysis perspective, based on Ernesto Laclau and Chantal Mouffe’s Theory of Discourse. Regarding the first objective, it was possible to note that the former participants declared that their entry in PBF was due to unemployment or underemployment. However, the demand for employment/salary is built in diferente ways: as a solicitation, reproducing discourses that contribute to the naturalization or individualization of problems; or as a demand, naming the reality of unemployment, poverty and hunger as social injustices resulting of poor management and corruption in the government, demanding the creation of employment and income. As to the PBF logics of functioning, it was possible to notice: a) a meritocratic and moralizing view towards those who are registered; b) the prevalence of a pork-barrel politics; c) deficiencies in the construction of exit doors. These aspects were seen as natural by the first group of people (legitimizing a pork-barrel relation), whereas for the second group, these aspects were problematized (questioning the nature of hostility and dependence produced). As to the second objective, the former participants that conceive their demands as a request do not politicize the location in society’s hierarchical order, attribute the responsibility for their living conditions to themselves. Those who build the demand as an exigence, conceive the condition of dissatisfaction as the denial of a right; so, name the condition of unemployment and poverty as oppression. Regarding the third objective, the former participants acknowledge the impacts produced by PBF in their lives through the increase of food consumption, the investment in the health and education of their kids and the feeling of economic freedom noticed among women who were registered. Researching how the former participants conceive PBF has allowed us to understand their discursive identifications and how they conceive the dominance relations in which they live; as well as the fact that PBF contributes to the acknowledgment of a greater plurality of demands in the public sphere, but produces challenges to the radicalization of democracy. This study contributes to the debate on public politics, mainly in the field of social welfare, and also to think of the psychosocial impacts of PBF in people’s lives and democracy.